Pengaruh Tingkat Pemberian Pakan Ikan Dengan Menggunakan Tepung Maggot Terhadap Pertumbuhan Dan Kelangsungan Hidup Benih Ikan Gurame (Oshpronemus Gouramy) - Zuriyanti, Siti; Juliana, Juliana; Mulis, Mulis (Fapertago, 2023)
This study aims to determine the effect of the proper fish feeding rate and dose by using maggot flour on the growth and survival of giant gurami (Oshpronemus Gouramy).this study was carried out within 30 days (june to july 2022) in Tatelu center for freshwater aquaculture fisheries (BPBAT),TATELU village,dimembe subdistrict,minahasa utara gerency,sulawesi utara province.the research implemented an experimental method using a complete randomizet design (RAL) consisting of four treatments and three test : treatmean A (dose 10% ), B (dose 15%),C (dose 20 %), and D (dose 25 %).the analysis of variance (ANOVA) on the length growth of giant gurami shows an insignificant effect (Sig > 0,05) that makes H0 confirmend and H1 rejected.concurrently,the analisis of varience (ANOVA) on the weight growth of giant gurame shows a significant result (Sig < 0,05) that makes H0 rejekted and H1 confirmed.the result also discloses that the proper dose is in treatment A (dose 10 %), obtained from 3,88 cm in length and 2,03 grams in weight of giant gurami.